Decomposing permanent and transitory poverty - Jan Goebel (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
This paper proposes a new method of calculating the proportion of permanently impoverished persons among persons in poverty as a whole. The paper shows that the widely used Shorrocks-Index for decomposing permanent and transitory inequality can also be acquired to describe poverty. This method overcomes certain difficulties involved in the methods of Rodgers & Rodgers (1993). The characteristics of the proposed Poverty-Stability-Index allow for an intuitive differentiation between the relative sizes of permanent and transitional poverty. Empirical results using data from the German Socio-Economic Panel (GSOEP) will be presented for East- and West-Germany. – – In der vorliegenden Arbeit wird eine neue Berechnungsweise des Anteils permanenter Armut an der gesamten vorhandenen Armut vorgestellt. Es wird gezeigt, dass der weithin genutzte Shorrocks-Index zur Zerlegung von permanenter und transitorischer Ungleichheit auch zur Beschreibung von Armut genutzt werden kann. Damit können Unzulänglichkeiten in der von Rodgers & Rodgers (1993) gewählten Berechnung behoben werden. Die Nutzung des hier vorgeschlagenen Armuts-Stabilitäts-Koeffizienten erlaubt eine gut interpretierbare Unterscheidung der relativen Größe von permanenter und transitorischer Armut. Empirische Ergebnisse werden anhand des Sozio-oekonomischen Panels (SOEP) für Ost- und Westdeutschland dargestellt.
Keywords: D63; I32; 330; Permanent poverty; transitory poverty; poverty dynamics; panel data; Armut; Dauer; Messung; Disparitätsmaß; Theorie; Deutschland; Shorrocks Index